PENGARUH ARUS KAS OPERASI, CAPITAL INTENSITY DAN UMUR PERUSAHAAN TERHADAP TAX AVOIDANCE - Siti Rahmawati (Yayasan Kayyis Mulia Jaya, 2026)
This study aims to determine the effect of Operating Cash Flow, Capital Intensity, and Company Age on Tax Avoidance. This type of research is quantitative research. The data used in this study is secondary data. The population used is finance companies listed on the Indonesia Stock Exchange (IDX) from 2018-2023. The sample in this study amounted to 14 companies over a 6-year period with a total sample of 84 selected using the Purposive Sampling method. This research data uses Eviews 12 software with descriptive tests, classical assumption tests, linear regression analysis tests, hypothesis tests. The results of this study indicate that Operating Cash Flow has no effect on Tax Avoidance, Capital Intensity has a significant effect on Tax Avoidance. Company Age has a negative effect on Tax Avoidance. Keywords: Arus Kas Operasi; Capital Intensity; Umur Perusahaan; Tax Avoidance.